Classifying bicycle sharing system use in Southern European island cities: cycling for transport or leisure? - Maas, Suzanne; Nikolaou, Paraskevas; Attard, Maria; Dimitriou, Loukas (My University, 2021)
Bicycle sharing systems (BSS) have been implemented in cities worldwide in an attempt to promote cycling. Cycling as a mode of transport has the potential to provide transport alternatives for those marginalized by car-based mobility, to reduce traffic related diseases and injuries, noise and air pollution, and to promote an active lifestyle and improve public health. The three Southern European island cities included in this research, Limassol (Cyprus), Las Palmas de Gran Canaria (Spain) and the Valletta conurbation (Malta), exhibit characteristics considered as barriers to cycling, such as hot summers and high humidity, hilliness and car-oriented culture and infrastructure. Thus far, cycling modal share is low: under 1%. However, bicycle sharing systems and policies promoting cycling have emerged in these cities too. In this research a year of trip data, shared by the BSS operators, is used to analyse the use of the BSS on a system and station level. An analysis of the origin-destination matrices highlights spatial patterns, and the assessment of different types of use captures user behaviour. Particular attention is paid to the influence of tourism on the system use, by analysing the spatial influence of tourist accommodation, points of interests and land use, by classifying BSS trips carried out for leisure or for transport, and by assessing the temporal influence of the tourist season. The comparative analysis between the three cities shows that despite sharing commonalities, the cities exhibit differences in their shared bicycle use.
Keywords: bicycle sharing systems (BSS); cycling; travel behaviour; Southern Europe